2013
DOI: 10.1002/ejoc.201300115
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical C–C Bond Formation between Alcohols and Olefins by an Environmentally Benign Radical Reaction

Abstract: A radical C–C bond formation between olefins and alcohols proceeded efficiently by simple light irradiation at room temperature. The reaction proceeded in the presence of commercially available tBuOOtBu without using the harmful elements and/or compounds that have an unpleasant smell that are often used in conventional radical reactions. In addition, the reaction did not require photosensitizers or photocatalysts, which eliminated the time‐consuming separation of sensitizers after the reaction, or the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…The change from nitrate to hydroxyl functional groups could affect gas-particle partitioning and aerosol yields if the organic nitrates and alcohols have different vapor pressures. However, previous studies have shown that hydroxyl groups lower the vapor pressure of an organic compound to the same extent as organic nitrate groups (Pankow and Asher, 2008). In this study, hydrolysis does not appear to be a major reaction pathway for β-pinene+NO 3 SOA under humid conditions.…”
Section: Effects Of Rh and Acidity On Soa Yieldscontrasting
confidence: 56%
See 2 more Smart Citations
“…The change from nitrate to hydroxyl functional groups could affect gas-particle partitioning and aerosol yields if the organic nitrates and alcohols have different vapor pressures. However, previous studies have shown that hydroxyl groups lower the vapor pressure of an organic compound to the same extent as organic nitrate groups (Pankow and Asher, 2008). In this study, hydrolysis does not appear to be a major reaction pathway for β-pinene+NO 3 SOA under humid conditions.…”
Section: Effects Of Rh and Acidity On Soa Yieldscontrasting
confidence: 56%
“…Matsunaga and Ziemann (2010) determined that highly oxidized gaseous organic compounds are lost to the chamber walls faster than compounds that have a lower degree of oxidation. Additionally, the gas wall partitioning coefficient for a specific compound has also been shown to increase with decreasing vapor pressure (Yeh and Ziemann, 2014), with highly oxidized species typically having lower vapor pressures than less oxidized species (Pankow and Asher, 2008). If vapor-phase wall loss is the driving factor for the decrease of organics in this study, it would be expected that oxidized compounds would be lost to the walls more rapidly.…”
Section: Aerosol Aging In the Darkmentioning
confidence: 72%
See 1 more Smart Citation
“…Matsunaga and Ziemann (2010) determined that highly oxidized gaseous organic compounds are lost to the chamber walls faster than compounds that have a lower degree of oxidation. Additionally, the gas wall partitioning coefficient for a specific compound has also been shown to increase with decreasing vapor pressure (Yeh and Ziemann, 2014), with highly oxidized species typically having lower vapor pressures than less oxidized species (Pankow and Asher, 2008). If vapor-phase wall loss is the driving factor for the decrease of organics in this study, it would be expected that oxidized compounds would be lost to the walls more rapidly.…”
Section: Aerosol Aging In the Darkmentioning
confidence: 73%
“…Two techniques have been developed: (1) the grafting of AA using H 2 O 2 instead of BP, and (2) the generation of carboxylic acid groups on the surface using only H 2 O 2 . In both techniques, instead of excited BP, carbon radicals are generated by H abstraction of photochemically generated OH radicals 12 (Scheme 2, right) and the generated carbon radicals are used for grafting AA or are reacted with O 2 to introduce carboxylic acid groups on the surface. The same dyeability with cationic dyes was obtained with techniques (1) and (2) but the latter has the advantage of requiring less chemicals.…”
Section: Introductionmentioning
confidence: 99%